Assessment Management in Higher Education - Al-Ali, Maytha (International Review of Management and Marketing, 2024)
This paper presents key findings from a study conducted with several universities in the GCC region regarding their approach and use of e-Assessment within their learning environments. The study identifies key factors that could impact the use and quality of e-Assessment, and describe how those factors could influence forming a consistent and effective approach to employ a long-term e-Assessment approach. Data was collected from several higher education institutions in the GCC region, using an online survey, in-depth interviews with academic administrators, and direct observation. The study identifies six critical factors that may have a direct or indirect impact on forming a consistent and effective approach to employ a long-term e-Assessment approach. Moreover, the study reveals a strong correlation between e-Assessment quality, and the centralization of e-Assessment strategy, e-Assessment administration, and e-Assessment Technology.